Photocatalytic Degradation of Rhodamine B Dye over Novel Porous TiO2-SnO2 Nanocomposites Prepared by Hydrothermal Method - Yan Wang; Zhaoli Yan; Xiaodong Wang (International Journal of Photoenergy)
The photocatalytic degradation of Rhodamine B dye was successfully carried out under UV irradiation over porous TiO2-SnO2 nanocomposites with various molar ratios of Ti/Sn (4–12) synthesized by hydrothermal method using polystyrene microspheres as template. The combination of TiO2 with SnO2 can obtain high quantum yield of TiO2, and then achieve the high photocatalytic activity. And its porous structure can provide large surface area, leading to more adsorption and fast transfer of dye pollutant. Structural and textural features of the samples were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), and N2 sorption techniques. Both adsorption and UV irradiation contribute to decolorization of about 100% of Rhodamine B dye over the sample TiSn10 after 30 min of the photocatalytic reaction, while the decomposition of Rhodamine B dye is only 62% over pure titania (Degussa P25).